2014
DOI: 10.1002/2013ms000259
|View full text |Cite
|
Sign up to set email alerts
|

A flux‐form conservative semi‐Lagrangian multitracer transport scheme (FF‐CSLAM) for icosahedral‐hexagonal grids

Abstract: A high-order incremental ''remap-type'' transport scheme is presented (FF-CSLAM). The scheme utilizes bi-quadratic polynomial subgrid-cell reconstruction functions based on the weighted least squares method. The integration of the reconstruction functions over flux areas, which is inherent in remap schemes, makes use of CSLAM approach of line integration. Though the formal order of the scheme is second order, yet quadratic subgrid scale polynomial reconstruction does lead to improvement in the overall accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…In order to attain more accurate interpolation results, high-order polynomial fitting was utilized. It needs a local grid stencil in 3D Cartesian spaces, and then the grid points in this local stencil would be mapped onto a local two-dimensional (2D) coordinate system by a general stereography projection [26,27], and then a bivariate polynomial was utilized to fit the values at grid points on the stencil. In order to obtain an approximate value at the departure point, first, find the nearest vertex for each departure point, and then a polynomial least-squares fit is calculated using values at the vertex and its nearest first-layer neighbor points.…”
Section: Local Polynomial Fitting By Least-square Methods (Poly-lsq)mentioning
confidence: 99%
“…In order to attain more accurate interpolation results, high-order polynomial fitting was utilized. It needs a local grid stencil in 3D Cartesian spaces, and then the grid points in this local stencil would be mapped onto a local two-dimensional (2D) coordinate system by a general stereography projection [26,27], and then a bivariate polynomial was utilized to fit the values at grid points on the stencil. In order to obtain an approximate value at the departure point, first, find the nearest vertex for each departure point, and then a polynomial least-squares fit is calculated using values at the vertex and its nearest first-layer neighbor points.…”
Section: Local Polynomial Fitting By Least-square Methods (Poly-lsq)mentioning
confidence: 99%
“…Potentially more accurate transport schemes, such as the one by Dubey et al (2014), are under consideration for future use. However, the trade-off between accuracy and computational effort remains an issue.…”
Section: Flux-corrected Transportmentioning
confidence: 99%
“…In this study, it was shown that the although Miura-simplification is unstable (depending on reconstruction function's order) for Courant numbers larger than approximately 1/2, but it can lead to more accurate solutions for low Courant numbers compared to rigorous remapping scheme on quadrilateral grid. Moreover the studies of [12,32] on icosahedral grids also pointed out that the geometrical errors (errors due to incorrect flux area approximation) are not as significant as the derivative errors (errors related to the sub-grid reconstructions). Therefore in second order advection scheme, where main source of error is derivative error, use of crude flux area simplification is justified.…”
Section: Finite Volume Advection Schemesmentioning
confidence: 99%